DELAYED BREAST RECONSTRUCTION WITH USING A TISSUE EXPANDER - A. D. Zikiryakhodzhayev; E. A. Rasskazova; A. Yu. Tukmakov (Исследования и практика в медицине)
The delayed reconstruction of the mammary gland after radical mastectomies is a surgical method for the rehabilitation of patients. Breast reconstruction using an expander is used in women with a small breast size, as well as in patients who refuse to use the patchwork methods for restoring the mammary gland. The article describes expansions, which were applied from the moment of their creation and those that are currently in use. Indications and contraindications to the delayed reconstruction of the mammary gland with the use of an expander are determined.The article presents the mammary gland marking and stages of delayed reconstructions performed in the department of oncology and reconstructive-plastic surgery of the breast and skin of the P. Hertsen MORI. In the case of a small size of the breast and the consent of patients for the use of implants, this reconstruction is the main surgical intervention. Rehabilitation of patients after radical mastectomies is a series of surgical interventions using expander techniques. At the 1st stage – the use of the expander, at the 2nd stage – the replacement of the expander for the implant, at the third stage – tatooing of areola and / or reconstruction of the nipple-areolar complex from its own tissues.Due to consistent surgical interventions, as well as the correction of the second breast, it is possible to achieve symmetry of the mammary glands, and, of course, to recreate the removed mammary gland.